A large food-borne outbreak of campylobacteriosis in kindergartens and primary schools in Pescara, Italy, May–June 2018. Issue 3 (21st March 2021) - Sorgentone, Simona; Busani, Luca; Calistri, Paolo; Robuffo, Giorgio; Bellino, Stefania; Acciari, Vicdalia; Ferri, Maurizio; Graziani, Caterina; Antoci, Salvatore; Lodi, Fabrizio; Alfonsi, Valeria; Cammà, Cesare; et al.
Abstract : Introduction. In May–June 2018, an outbreak of campylobacteriosis involved students and school staff from kindergartens and primary schools in Pescara, southern Italy. Aim. We present details of the epidemiological and microbiological investigation, and the findings of the analytical study, as well as the implemented control measures. Methodology. To identify possible risk factors associated with the observed outbreak, a case control study was conducted using a questionnaire to collect information on the date of symptoms onset, type and duration of symptoms, type of healthcare contact, school attendance, and food items consumed at school lunches during the presumed days of exposure. Attack rates were calculated for each date and school. Logistic regression models were used to estimate the odds ratios of being a case and the odds of illness by food items consumed, respectively. Moreover, we carried out a comparative genomic analysis using whole genome multilocus sequence typing (wgMLST) of Campylobacter jejuni strains isolated during the outbreak investigation to identify the source of the outbreak. Results. Overall, 222 probable cases from 21 schools were identified, and C. jejuni was successfully isolated from 60 patients. The meals in the schools involved were provided by two cooking centres managed by a joint venture between two food companies. Environmental and food sampling, epidemiological and microbiological analyses, as well as a case control study with 176 cases and 62 controls from the same schools were performed to identify the source of the outbreak. The highest attack rate was recorded among those having lunch at school on 29 May (7.8 %), and the most likely exposure was 'caciotta' cheese (odds ratio 2.40, 95 % confidence interval 1.10–5.26, P =0.028). C. jejuni was isolated from the cheese, and wgMLST showed that the human and cheese isolates belonged to the same genomic cluster, confirming that the cheese was the vehicle of the infection. Conclusion. It is plausible that a failure of the pasteurization process contributed to the contamination of the cheese batches. Timely suspension of the catering service and summer closure of the schools prevented further spread.